Pengembangan Wirausaha Berbasis Lingkungan: Pemberdayaan Masyarakat Melalui Pengolahan Limbah Dan Produk Kreatif Di Kelurahan Betungan - Sagita, Zendy HD; Saputra , Tedi Alvian; Hutagal, Joshua Panahatan; Saputra, Jejen Pertama; Nurohim, Andika; Jusmadi , Evryeni; Mujiono, Mujiono; Nur’aini, Hesti (Universitas Dehasen Bengkulu, 2025)
The Kuliah Kerja Nyata (KKN) program in Betungan Village, Bengkulu City, focuses on the development of environment-based entrepreneurship through the processing of household waste into products of economic value. The main activities include training in making compost from organic waste, making decorative plant pots from used materials, and community empowerment in creative recycling. The goal of this program is to reduce the volume of waste while increasing the income of local communities through the concept of social entrepreneurship in the environmental field. Implementation methods include education, participatory training, and small business mentoring. Results showed the community's enthusiasm in processing organic waste into compost and inorganic waste into craft products, with promising economic potential. A simple SWOT analysis indicated strengths in the availability of waste raw materials and community support, opportunities in the form of increasing demand for environmentally friendly products, but weaknesses such as limited business skills and threats from business sustainability. This service-learning activity concluded that environmental initiatives can be developed into local business opportunities through social entrepreneurship, with the support of further training and stakeholder collaboration.